lncRNA IGF2 AS Regulates Bovine Myogenesis through Different Pathways - Chengchuang Song; Zhaoxin Yang; Rui Jiang; Jie Cheng; Binglin Yue; Jian Wang; Xiaomei Sun; Yongzhen Huang; Xianyong Lan; Chuzhao Lei; Hong Chen (Elsevier, 2020)
The role of long non-coding RNA (lncRNA) in the regulation of bovine skeletal muscle development remains poorly understood. The present study investigated the function and regulatory mechanism of a novel lncRNA, insulin-like growth factor 2 antisense transcript (IGF2 AS), in bovine myoblast proliferation and differentiation. Gain or loss of IGF2 AS was performed using an expression plasmid or small interfering RNA (siRNA), respectively. Bovine myoblasts were used to investigate the biological function and mechanisms of IGF2 AS in vitro. Results were conjointly analyzed by celluar and molecular biology experiments as well as bioinformatics. Functionally, IGF2 AS could promote proliferation and differentiation of bovine myoblasts. The preliminary mechanism suggests, on the one hand, that IGF2 AS could complement the IGF2 gene intron region and affect the stability and expression of IGF2 mRNA. On the other hand, RNA pull-down and immunoprecipitation assays demonstrated that IGF2 AS could directly bind to the interleukin enhancer binding factor 3 (ILF3) protein and maybe partly though it to regulate myogenesis. In conclusion, the novel identified lncRNA IGF2 AS promoted proliferation and differentiation of bovine myoblasts through various pathways.